69.1k views
3 votes
Write the equation of the graph shown below in factored form.

1. f(x) = (x − 3)(x + 1)(x + 4)
2. f(x) = (x + 3)(x − 1)(x − 4)
3. f(x) = (x + 3)(x + 1)(x + 4)
4. f(x) = (x − 3)(x − 1)(x − 4)

Write the equation of the graph shown below in factored form. 1. f(x) = (x − 3)(x-example-1
User Judee
by
5.4k points

2 Answers

5 votes

Answer:

2. f(x) = (x + 3)(x − 1)(x − 4)

Explanation:

As we know that, the standard factored form of an cubic polynomial is:

f(x)= a(x -
r_(1))(x -
r_(2))(x -
r_(3)) where:
r_(1) ,
r_(2),
r_(3) are the roots or x-intercept of the function when it is equal to 0.

In this situation, we can see that:


  • r_(1) = 4

  • r_(2) = 1

  • r_(3) = -3
  • a = 1

So the the equation of the graph shown is:

f(x) = a(x -
4)(x -1)(x +3)

We choose 2, hope it will find you well.

User Lucasviewup
by
5.1k points
4 votes

Answer:

2. f(x) = (x + 3)(x − 1)(x − 4)

Explanation:

The roots of this polynomial graph are the x-intercepts.

These are x=-3, x=1, x=4

These implies that the factors of the function are:

(x+3), (x-1), and (x-4)

The factored form is given as:


f(x) = (x + 3)(x - 1)(x - 4)

Therefore the second option is correct.

User BoygeniusDexter
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.